Study on the impact of the Covid-19 pandemic on the national unemployment rate - Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
In this article I set out to present the situation in terms of unemployment rate, the number of registered unemployed but also the share of unemployed nationwide in the period 2020-2021. Due to the Covid-19 pandemic, the unemployment rate has increased considerably. The provisions of the military ordinances on stopping the new virus have caused many companies to partially or even completely cease their activity, many people being left without a job, they being helped by the state with a technical unemployment benefit, which led to the highest unemployment rate in the last two years, resulting in a deficient economy. The research method used in the study undertaken is the statistical processing and economic analysis of existing data for the period 2020-2021 on specialized sites such as the National Institute of Statistics, Ministry of Labor and Social Protection, Eurostat, FAO, Ministry of Agriculture and Rural Development but also other specialized materials.
Keywords: C13; J60; J20; 330; unemployment rate; pandemic; unemployed